2009
DOI: 10.2131/jts.34.sp229
|View full text |Cite
|
Sign up to set email alerts
|

Children's toxicology from bench to bed - Liver Injury (3): Oxidative stress and anti-oxidant systems in liver of patients with wilson disease

Abstract: -The role of oxidative stress in the pathogenesis of liver disease in Wilson disease (WD), a genetic disorder characterized by excess hepatic deposition of copper, which generates free radicals, remains unclear. This study investigates oxidative stress on the liver and hepatic anti-oxidant responses in WD using liver specimens from affected patients showing mild liver damage (group I, n = 3), moderate or greater liver damage (group II, n = 5) and fulminant hepatic failure (group III, n = 5), and from asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As expected, we found a lower TAC in our patients with WD, most probably due to oxidative stress induced by accumulated copper (Videla et al 2003). This is consistent with decreased levels of different antioxidants (Sinha et al 2005), and increased oxidative stress (Nagasaka et al 2009, Ogihara et al 1995 previously reported. However, in none of these studies were differentiations performed between the hepatic or neurological forms of WD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, we found a lower TAC in our patients with WD, most probably due to oxidative stress induced by accumulated copper (Videla et al 2003). This is consistent with decreased levels of different antioxidants (Sinha et al 2005), and increased oxidative stress (Nagasaka et al 2009, Ogihara et al 1995 previously reported. However, in none of these studies were differentiations performed between the hepatic or neurological forms of WD.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, copperinduced free-radical formation, lipid peroxidation (Videla et al 2003), and subsequent oxidative damage of hepatocytes' mitochondria are reported to be crucial in WD pathogenesis (Sokol et al 1994). In fact, decreased levels of different antioxidants and increased oxidative stress (Nagasaka et al 2009, Ogihara et al 1995) have been described, using different methods, in patients with the hepatic presentation of WD (Nagasaka et al 2006). Experiments using HepG2 cells have shown that proteins involved in antioxidant defense are dramatically altered by chronic copper exposure (Jimenez et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Copper-associated hepatic injury results in decreases in hepatic and plasma glutathione and vitamin E concentrations. 25,26,[31][32][33][34] Because de novo hepatic synthesis of glutathione is the predominant source of plasma glutathione and plays a vital role in glutathione homeostasis, copper-associated hepatic injury can have widespread systemic consequences (eg, exacerbation of oxidative injury caused by concurrent illnesses).…”
Section: Hepatic Injury Association With Copper Accumulationmentioning
confidence: 99%
“…Oxidative Stress Promotes Clusterin Interaction with ATP7B-Clusterin activity is initiated in response to cellular stresses (17,20), and both copper excess and deficiency are known to cause oxidative stress in cells (31,32). To determine whether the interaction is modulated directly by oxidative stress, co-immunoprecipitation experiments were repeated using HepG2 cells treated with either H 2 O 2 (20 min) or diamide (15 min) (Fig.…”
Section: Fluctuations In Intracellular Copper Promotes Clusterinmentioning
confidence: 99%